Degradation of the human proteinase inhibitors alpha-1-antitrypsin and alpha-2-macroglobulin by Bacteroides gingivalis. - Carlsson, J (1984)
Various strains of black-pigmented Bacteroides species were grown on horse blood agar and suspended in human serum. After various times of incubation the effect of the bacteria on the serum was evaluated by polyacrylamide gel electrophoresis and "rocket" immunoelectrophoresis. The formation of trichloroacetic acid-soluble material in the suspensions and the capacity of the treated sera to inhibit the activity of trypsin were also determined. The two tested strains of Bacteroides gingivalis (W83, H185) degraded most serum proteins, including the plasma proteinase inhibitors alpha-1-antitrypsin and alpha-2-macroglobulin. They did not, however, degrade alpha-1-antichymotrypsin. Bacteroides intermedius NCTC 9336, Bacteroides asaccharolyticus NCTC 9337, and an asaccharolytic oral strain different from B. gingivalis (BN11a-f) did not degrade the plasma proteinase inhibitors. These strains were, however, able to inactivate the capacity of serum to inhibit the activity of trypsin.